2020
DOI: 10.3390/ijerph17041439
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Population Aging and Public Health Support on EU Labor Markets

Abstract: Population aging and public health expenditure mainly dedicated to older dependent persons present major challenges for the European Union (EU) Member States, with profound implications for their economies and labor markets. Sustainable economic development relies on a well-balanced workforce of young and older people. As this balance shifts in favor of older people, productivity tends to suffer, on the one hand, and the older group demands more from health services, on the other hand. These requisites tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(100 citation statements)
references
References 37 publications
3
94
0
3
Order By: Relevance
“…Furthermore, the mortality rate and incidence of COVID-19 could be associated with air pollution and the average age of the population. It seems that older populations in the northern hemisphere, especially in Europe and North America with a higher income, have a higher death rate from respiratory infections (Michel, 2010;Cristea et al, 2020;Knickman and Snell, 2002;Eurostat, 2019). Additionally, it seems that air pollution plays a determinative role in COVID-19 outbreak and mortality.…”
Section: Tablementioning
confidence: 99%
“…Furthermore, the mortality rate and incidence of COVID-19 could be associated with air pollution and the average age of the population. It seems that older populations in the northern hemisphere, especially in Europe and North America with a higher income, have a higher death rate from respiratory infections (Michel, 2010;Cristea et al, 2020;Knickman and Snell, 2002;Eurostat, 2019). Additionally, it seems that air pollution plays a determinative role in COVID-19 outbreak and mortality.…”
Section: Tablementioning
confidence: 99%
“…In this way, companies are very attentive to the requirements of different categories of stakeholders, given their involvement which are no longer mere spectators of the economic phenomenon, but sanction the inappropriate actions of companies such as those in highly polluting industries or those whose activity has an impact on public health, encouraging their decisions the activity of companies that have adopted the principles of sustainable development. Thus, consumers base their product purchasing decisions on issues related to the behavior of manufacturing companies towards the environment, public health or local communities, and portfolio investors consider additional criteria for selling and buying financial securities such as corporate social responsibility, thus fueling the process of divestment from polluting companies and the process of investing in environmentally friendly companies (Panait et al, 2014;Lombardi et al, 2015;Palazzo et al, 2016;Cristea et al, 2020). Reality has shown that CSR is not a simple tool for involving companies in society or in the community, it is not a marketing technique but a component of the management strategy that fuels the company's long-term competitive advantage (Genier et al, 2009;Matei, 2013) by generating favorable attitudes from stakeholders, by creating a business opportunity, by the emergence and integration of new tools through which we witness business reengineering (for example social investment).…”
Section: Csr Implication In Agri-food Sectormentioning
confidence: 99%
“…Aging of the world population is as undeniable as its profound health and economic consequences (15). The increased average age at which women have children and the consequent increase in problems related with fertility are the principal causes that lead to an increase in the demand for assisted reproduction technologies (16,17).…”
Section: Discussionmentioning
confidence: 99%